Dissolution of chitosan nanocrystals in aqueous media of different acidity. Molecular dynamic study. (1st March 2019) - Naumov, Vladimir S.; Ignatov, Stanislav K.
Graphical abstract: Highlights: Dissolution of chitosan nanocrystals have been studied using molecular dynamics. Calculated constants are in good agreement with available experimental data. Dissolution rate dependence on polymer molecular structure is estimated. Dissolution rate dependence on media acidity is estimated. Abstract: The process of dissolution of chitosan nanocrystals with molecular mass of polymer up to 12.8 kDa in aqueous media of various pH was studied by molecular dynamic simulations with the use of the improved force field GROMOS 56ACARBO_CHT specially developed for the chitosan polymers description. The effect of the media acidity and polymer molecular weight on the dissolution process kinetics has been studied and the regression expressions for kinetic parameters were established. The calculated solution viscosity, Mark–Houwink–Sakurada equation parameters, and pH values of the dissolution beginning are in good agreement with the available experimental data. The uniform/non-uniform distribution of protonated amino groups and hydrogen bonds along the polymeric chains is found to be of key importance parameter for the dissolution process which can be considered as a criterion of dissolution ability.